Enhancement of the 808 nm Photothermal Effect of Gold Nanorods by Thiol‐Induced Self‐Assembly. (24th February 2014) - Sheng, Yu; Lin, Min; Li, Xiangwei; Hao, Hongxia; Lin, Xiaoying; Sun, Hongchen; Zhang, Hao
<x xml:space="preserve">Abstract</x> Gold (Au) nanomaterials are promising photothermal agents for the selective treatment of tumor cells owing to the strong capability to convert near‐infrared (NIR) irradiation into heat energy. One basic issue for practical photothermal therapy is the enhancement of photothermal effect in NIR region. Here, various low‐molecular‐weight thiols are applied to induce one‐dimensional (1D) self‐assembly of Au nanorods (NRs), which leads to the redshift of absorption peak towards NIR region. As a result, the 1D assembled Au NRs exhibit improved photothermal effect at 808 nm in comparison to unassembled Au NRs.